Performance analysis of space-time block-coded multitone CDMA system - YANG Wei1; WANG Xin-sheng1 (Tongxin xuebao)
A space-time block-coded multitone code-division multiple-access（STBC MT-CDMA） system was proposed.The uplink bit error rate（BER） performance of the proposed system with maximum ratio combining（MRC） was theoretically analyzed in a multipath fading channel and the corresponding BER expressions were derived,which was verified through simulations.Numerical results show that the BER performance,error floor and capacity of the proposed system are improved significantly due to the joint space-time and path gain.